Prototype of Air Quality Sensor for Gas Pollutants Monitoring System in Industrial and Residential Estates - Enndi Chiu; Joni Welman Simatupang; Rijal Hakiki; Filson Maratur Sidjabat (Jetri : Jurnal Ilmiah Teknik Elektro, 2021)
Globalization causes the industrial and information era to develop in massive ways to produce and distribute goods for human needs using big trucks. Due to massive transportation passing by, it is also required to monitor the the level of gases pollutants that can endanger the human respiratory system. This work presents the integrated sensor consists of Arduino Uno and Raspberry Pi 1 Model B+ that can monitor 3 different parameters such as CO, CO2, and NH3 to monitor the industrial area in Lippo Cikarang for the measurement. For monitoring system, the author uses Node-RED for implementing the internet of things system. For gas sensor, author uses MQ-135 air quality sensor to detect 3 gases parameters which have been mentioned with graphs. The main goal of this work is to contribute data for monitoring system of gas pollutants in industrial and residential areas. The experiment has been successfully done where table and graph are shown to be analyzed and summarized. Measurement results are then compared with the environmental air quality standard. As conclusion, the average level of ppm in industrial area for CO2 is 30 ppm, for NH3 is 28.9 ppm, and for CO is 27.08 ppm. While, the average level of ppm in residential area for CO2 is 21.32 ppm, for NH3 is 19.3 ppm, and for CO is 20.93 ppm.  Globalisasi menyebabkan era industri dan informasi berkembang pesat dalam memproduksi dan mendistribusi barang – barang untuk kebutuhan manusia menggunakan truk. Karena banyak transportasi yang lalu lalang, diperlukan divais untuk memonitor kadar polutan gas yang dapat membahayakan sistem pernapasan manusia. Penelitian ini menyajikan sensor terintegrasi yang terdiri dari Arduino Uno dan Raspberry Pi 1 Model B+ yang dapat memonitor 3 jenis gas yang berbeda seperti CO, CO2, and NH3 di area industri. Untuk sistem monitor, penulis menggunakan Node-RED untuk implementasi sistem Internet of Things (IoT). Untuk sensor gas, penulis menggunakan sensor kualitas udara MQ-135 untuk mendeteksi 3 jenis gas yang sudah disebutkan dengan kalibrasi dan grafik agar dapat memonitor tingkatan polutan gas. Tujuan utama dari penelitian ini adalah untuk memberikan kontribusi hasil data untuk sistem monitoring gas polutan di kawasan industri dan perumahan. Eksperimen sudah dilakukan dengan baik dimana tabel dan grafik ditampilkan untuk dianalisis dan dirangkum. Hasil dari pengukuran dibandingkan dengan standar baku mutu lingkungan. Rata – rata level dari ppm di area industri untuk CO2 adalah 30 ppm, untuk NH3 adalah 28.9 ppm, dan untuk  CO adalah 27.08 ppm. Dan juga rata – rata level dari ppm di tempat warga tinggal (perumahan) untuk CO2 adalah 21.32 ppm, untuk NH3 adalah 19.3 ppm, dan untuk CO adalah 20.93 ppm.